The Influence of Leadership Style and Work Discipline on Employee Performance with Work Motivation as an Intervening Variable at PT. Permodalan Nasional Madani Bogor Branch Office - Henny Herawaty (International Journal of Asian Business and Management, 2023)
The key factors affecting performance are employees and work discipline. Work motivation as an intermediate variable in the relationship between leadership style and employee performance at the PT PNM Bogor Branch Office. Employee performance at the PT Permodalan Nasional Madani Bogor Branch Office will be analysed in relation to the researcher-identified leadership style, work discipline, and work motivation. A total of 120 employees from various departments at the PT PNM Bogor Branch Office were randomly selected to participate in the study. PLS SEM is a statistical approach used for analysing data. Findings from studies conducted at the PT PNM Bogor Branch Office indicate that a leader's style influences workers' motivation (Y1) but has no effect on productivity (Y2). Employee performance (Y2) is positively impacted by work discipline, and employee motivation to work (Y1) is influenced by work discipline as well. The degree to which workers are inspired by their jobs is a key factor in their productivity (Y2). In addition, there is a nuanced mediational relationship: leadership style affects performance via the complete intermediary of work motivation, while work discipline affects performance both directly and via the partial intermediary of work motivation